Spin Art Painting as Therapeutic Intervention for Improving Learning Expression Participation Behavior in Children with Special Needs - Ramadhan, Fachri; Yunus, Pangeran Paita; Sukarman B, S B (Journal of Innovation and Research in Primary Education, 2025)
Children with special needs often experience challenges in learning expression participation behavior due to monotonous conventional art instruction that fails to accommodate their psychological and sensory needs. This study examined the implementation of spin art painting technique as therapeutic intervention to improve learning expression participation behavior among students with special needs. This classroom action research employed qualitative descriptive approach following Kemmis and McTaggart's model across three stages: pre-cycle, cycle I, and cycle II. Conducted at UPT SLB Negeri 1 Makassar, the study involved twelve purposively selected students with diverse special needs (deaf, intellectual disabilities, autism spectrum disorder, and multiple disabilities). Data were collected through systematic observation, semi-structured interviews, and documentation, then analyzed using qualitative descriptive procedures involving data reduction, display, and conclusion drawing. Progressive behavioral improvements were documented across intervention phases, with quantitative behavioral scores advancing from 46.95 (pre-cycle) to 65.68 (cycle I) and 77.54 (cycle II), representing 65.2% overall improvement and surpassing established minimum competency criteria. Students demonstrated enhanced attention, self-control, discipline, focus, active involvement, social interaction, and emotional expression. The technique's process-oriented, multi-sensory nature successfully engaged students across all disability categories, transforming previously passive or disruptive behaviors into focused, emotionally expressive engagement. Spin art painting effectively functions as therapeutic medium for improving learning expression participation behavior in special education contexts. The technique's experimental nature, unpredictable outcomes, and elimination of performance pressure create psychologically safe environments promoting exploration and emotional expression. Findings validate child-centered art education philosophy while offering accessible, replicable intervention applicable across resource-constrained educational settings.